PRELIMINARY STUDY NORMALIZED DIFFERENCE WATER INDEX IN THE RECHARGE AREA OF GROUND WATER OF BEKASI DISTRICT - Darul, Achmad; Irawan, Dasapta Erwin; Roekmi, Raden Ajeng Koesoemo; Oktavia, Putu (Jurnal Pendidikan Geografi Gea, 2017)
In term of groundwater conservation, the aim of this research is to identify normalized difference water index (NDWI) in rock composition region of Qav (conglomerate, sandstone, tuffaceous, tuff, and breccia) which is the recharge area of groundwater deposit in Kabupaten Bekasi, as identified by a stable isotope research in 2001. This research analyzes the NDWI mapping from open access data from high-resolution satellite images and multispectral Sentinel-2. The data is obtained from 20th May 2016 mapping on dry season. The analyze is conducted using QGIS open source software which is accommodated with semi-automatic classification open source plugin. The result shows that the NDWI can be classified into six categories from the lowest value of -1 (low index) to 1 (high index) in Kecamatan Cileungsi Kabupaten Bogor, Kecamatan Setu Kabupaten Bekasi and Kecamatan Bantargebang Kota Bekasi